Effectiveness of Mindfulness Based Intervention: Open Heart Prayer in Diabetic Ulcer Patients at X Bekasi Hospital - Frian Apituley; Dewi Prabawati; Sudibyo Supardi (Al Makki Health Informatics Journal, 2024)
Diabetic ulcers are open wounds on the skin surface accompanied by necrotic tissue. Patients with diabetic ulcers tend to experience a significant increase in emotional distress, where individuals will feel negative emotions in daily life. This study aims to determine the effectiveness of mindfulness-based intervention: Open Heart prayer on emotional distress and blood sugar levels in diabetic ulcer patients at X Bekasi Hospital. This study used a quasi-experimental method with a two-group pre-test and post-test approach, involving 98 samples divided into a control group (49) and an intervention group (49). Open Heart prayer therapy was given 4 times a week for 4 weeks, with the research instrument being the DASS 42 questionnaire. The results showed a significant relationship between mindfulness-based intervention: Open Heart prayer in reducing emotional distress in the intervention group before and after the intervention (p-value <0.001). Diabetic ulcer patients who underwent Open Heart prayer experienced a 1-time decrease in emotional distress compared to patients who did not undergo the intervention. In addition, the decrease in emotional distress had an impact on reducing blood sugar levels (p-value <0.001). Patients who experienced a decrease in emotional distress showed a decrease in fasting blood sugar levels by 12 times (Exp (B) = 11.795) compared to patients whose emotional distress increased.  Mindfulness-Based Intervention Therapy: Open Heart prayer proved to be effective in helping reduce emotional distress and fasting blood sugar levels in diabetic ulcer patients. Multivariate results showed that the risk factors of gender and degree of injury had a significant effect (p-value <0.05) in reducing emotional distress, while age and degree of DM also had a significant effect (p-value <0.05) in reducing emotional distress.